Evaluation of growth and foraging in laboratory colonies of Coptotermes gestroi (Isoptera, Rhinotermitidae) - Janei, Vanelize [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Elsevier B.V., 2015)
Coptotermes gestroi is an exotic species in Brazil that forages on several food items at the same time. Different laboratory tests were performed with 6-year-old colonies of this termite in order to follow the development and displacement of these colonies, considering which castes and instars were transferred or moved from their original chamber. Two bioassays were carried out, one with similar alternative foods (Pinus sp. sawdust), and the other with different alternative foods (large block of Pinus taeda and small block of Pinus elliottii). The colonies of C. gestroi did not show preferences in the allocation of foragers when they had alternative similar foods. However, they were found in the chamber that contained the small block of P. elliottii, when termites had the alternative of different blocks of Pinus, indicating an environment most favorable for the nucleus of the colony (royal cup and brood). Many factors may have influenced this choice as more nutritive alimentary resource for brood or the presentation of the food, which allowed better colony accommodation. C gestroi did not have difficulties of migration from one chamber to another and this characteristic may be a risk factor in urban infestations of this severe pest.
Keywords: Caste allocation; Complete colonies; Subterranean termites; Urban pest